(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ieamkheng S, Santibenchakul S, Sooksawat N. 2022. Potential of Maranta arundinacea residues for recycling: Analysis of total phenolic, flavonoid, and tannin contents. Biodiversitas 23: 1204-1210. The potential of Maranta arundinacea L. residues was evaluated for their nutrient composition as organic fertilizer and for the presence of the total phenolic, flavonoid, and tannin contents as phytochemical resources. This arrowroot was collected from seven different locations and planted under organic conditions. The leaves contain 1.28% total nitrogen (total N) and 1.71% total potassium (total K) that might be used as an organic component in fertilizer. The stems contain 3.25% moisture and a C/N ratio of 81.45 which might serve as the good mulch. The total phenolic, flavonoid and tannin contents of M. arundinacea differed in different plant parts (leaves, stem, rhizome residue), age (6, 9, 12 months), and sampling locations (Th-TK, Th-R, Th-SyK, Th-Kpc, Th-Chan, Th-Sk, Kh-B). The high total phenolic content was obtained from the Th-Kpc leaves at the 6-month-old plant (0.268 mg GAE)/g DW). The high total flavonoid content was obtained from the Kh-B rhizome residue at the 9-month-old plant (0.379 mg QE)/g DW). The high total tannin content was obtained from the Th-Chan rhizome residue at the 9-month-old plant (4.746 mg tannin/g DW). This study indicated that the rhizome residues were an abundant source of total tannin; that might be potential to be used in the food and medicinal industries. Leaves and stem residues might be useful in organic farming.